‘In a dark place, we find ourselves’: light intensity in critical care units - Durrington, H; Clark, R; Greer, R; Martial, F; Blaikley, J; Dark, P; Lucas, R; Ray, D (Springer Open, 2017)
Intensive care units provide specialised care for critically ill patients around the clock. However, intensive care unit patients have disrupted circadian rhythms. Furthermore, disrupted circadian rhythms are associated with worse outcome. As light is the most powerful ‘re-setter’ of circadian rhythm, we measured light intensity on intensive care unit. Light intensity was low compared to daylight during the ‘day’; frequent bright light interruptions occurred over ‘night’. These findings are predicted to disrupt circadian rhythms and impair entrainment to external time. Bright lighting during daytime and black out masks at night might help maintain biological rhythms in critically ill patients and improve clinical outcomes.